The effect of mesocarbon microbeads on magnetorheological fluid behavior. (March 2022) - Pierce, Rebecca; Choi, Young-Tai; Wereley, Norman M
Magnetorheological (MR) fluids are composed of magnetizeable particles suspended in a carrier fluid and change apparent viscosity upon the application of a magnetic field. Previous studies have shown that passive particles, such as hollow glass spheres, can augment the yield stress of MR fluids, but this yield stress augmentation has limited endurance because the hollow glass microspheres are not sufficiently durable. This study evaluates mesocarbon microbeads (MCMBs) as an alternative passive particle with the potential for MR yield force augmentation but with greater durability. The yield properties of six MR fluid concentrations with varying carbonyl iron particle (CIP) and MCMB volume fractions were tested using a shear mode rheometer and flow mode MR damper. MCMBs did not augment yield stress in shear mode, but, in contrast, in flow mode, the yield force increased nonlinearly with MCMB volume fraction. Furthermore, this yield force-enhancing effect did not diminish over 100, 000 cycles (or 5 km of piston travel). The theoretical non-dimensional plug thickness which arises from an approximate parallel plate analysis of a fluid element in flow mode is used illustrate to a potential mechanism for the yield force augmentation effect.